Retypification of Bignonia marginata (Bignoniaceae) - Arbo, Maria M. (Phytotaxa, 2016)
Adenocalymma marginatum (Cham.) DC. is a Neotropical liana, with yellow flowers that grows on humid forests from Southern South America. The revision of Bignoniaceae type materials of species native to Argentina raised the need for a new typification of Bignonia marginata Chamisso, the basionym of Adenocalymma marginatum (Cham.) DC. A neotype and a holotype were designated for the basionym by previous workers. I here designate a lectotype for Bignonia marginata that is part of the original material, superseding the previous typifications.